DESIGNING SPEAKING MATERIAL FOR ENGLISH CONVERSATION CLUB (ECC) STUDENTS OF SMAN 2 KOTA PEKALONGAN - Muhammad Ivan Fauzi (PRASASTI: Journal of Linguistics, 2019)
The objectives of this study are: 1) to identify the target and learning needs of English Conversation Club students in learning English and 2) to design English learning materials for English Conversation Club in SMAN 2 Kota Pekalongan.This research is classified into Research and Development (R & D). This research was conducted through the following steps i.e.; (1) conducting the needs analysis, (2) analyzing syllabus, (3) designing the material. The subjects of this research were the ECC students of grade ten in SMAN 2 Kota Pekalongan. The data were collected by distributing questionnaires to the students. The questionnaires were administered to find out the needs of the ECC students in learning English.In this research, the researcher designed three units of learning materials with eight tasks in each unit. They are ‘Congratulation’, ‘Complimenting’, and ‘Accepting and Refusing Invitation’.Key Words: Learning Materials, Speaking, ECC